The book of books : biblical interpretation, literary culture, and the political imagination from Erasmus to Milton - Fulton, Thomas (Thomas Chandler) (University of Pennsylvania Press, 2021)
"In The Book of Books, Thomas Fulton charts the process of recovery, interpretation, and reuse of scripture in early modern English literary culture, exploring the uses of the Bible as a combination of text and paratext that revolved around sites of social controversy and was continually transformed for political purposes. In The Book of Books, Thomas Fulton charts the process of recovery, interpretation, and reuse of scripture in early modern English literary culture, exploring the uses of the Bible as a combination of text and paratext that revolved around sites of social controversy and was continually transformed for political purposes." --